John Capgrave's Fifteenth Century - Winstead, Karen A. (Karen Anne), 1960- (Book collections on Project MUSE., 2007)
Rejecting the prevalent view of Capgrave as predictably conservative, John Capgrave's Fifteenth Century contributes to a broader appraisal of fifteenth-century culture and offers a fresh view of orthodoxy and dissent in pre-Reformation England.